2017
DOI: 10.1039/c7cy00945c
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of unsaturated carbonyls by Ni–Fe-based alloy catalysts

Abstract: Ni–Fe alloy catalysts prepared by a simple hydrothermal method and subsequent H2 treatment were shown to be highly selective for the hydrogenation of various unsaturated carbonyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…However, the di‐σ CO and end‐on mode enhanced the reactivity for C=O group and generated the desired alcohols. For the Pt−Fe(Ni 3 )/UiO‐66 catalytic system, C=O group was activated and weakened via end‐on bonding interaction (Δ E ads =−0.45 eV) on the electron‐deficient Fe surface, which attributed to the lone pair of oxygen for carbonyl group can be attracted preferentially because of anticlinal folded Pt−Fe skin (Figure S14) [24] . Meanwhile, the dissociated hydrogen molecules are transferred to attack and activate CAL to form COL. For the Pt‐Ni 3 /UiO‐66 catalytic system, the differences in product distribution can be rationalized based on the extended Huckel calculations of Delbecq and Sautet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the di‐σ CO and end‐on mode enhanced the reactivity for C=O group and generated the desired alcohols. For the Pt−Fe(Ni 3 )/UiO‐66 catalytic system, C=O group was activated and weakened via end‐on bonding interaction (Δ E ads =−0.45 eV) on the electron‐deficient Fe surface, which attributed to the lone pair of oxygen for carbonyl group can be attracted preferentially because of anticlinal folded Pt−Fe skin (Figure S14) [24] . Meanwhile, the dissociated hydrogen molecules are transferred to attack and activate CAL to form COL. For the Pt‐Ni 3 /UiO‐66 catalytic system, the differences in product distribution can be rationalized based on the extended Huckel calculations of Delbecq and Sautet.…”
Section: Resultsmentioning
confidence: 99%
“…For the PtÀ Fe(Ni 3 )/ UiO-66 catalytic system, C=O group was activated and weakened via end-on bonding interaction (ΔE ads = À 0.45 eV) on the electron-deficient Fe surface, which attributed to the lone pair of oxygen for carbonyl group can be attracted preferentially because of anticlinal folded PtÀ Fe skin ( Figure S14). [24] Meanwhile, the dissociated hydrogen molecules are transferred to attack and activate CAL to form COL. For the Pt-Ni 3 /UiO-66 catalytic system, the differences in product distribution can be rationalized based on the extended Huckel calculations of Delbecq and Sautet. As shown in Table S6, Ni species showed unstable four-electron interactions due to a narrower d-band width compared to Fe, and the strong interactions between the conjugated C=C bond and the Ni surface form di-σ mode (ΔE ads = À 1.18 eV) lead to the favorable adsorption behavior of C=C group, thereby notably enhancing the catalytic selectivity of CAL.…”
Section: Substratesmentioning
confidence: 99%
“…The addition of Ru promoted the reduction of Mo to strengthen the hydrogenation capacity of it. Putro et al (2017) synthesized a Ni-Fe alloy catalyst by using a hydrothermal method that achieved high selectivity in the hydrogenation of furfural. The result suggested that the electrondeficient Fe can weaken and activate the C=O bonds through a side bonding interaction of the lone pair of oxygen in the carbonyl group, making π-complexing occur between the C=O bonds and the Ni atoms, as shown in Figure 4.…”
Section: Bimetallic Catalystsmentioning
confidence: 99%
“…Plausible mechanism for the selective hydrogenation of unsaturated alcohols over Ni-Fe-based alloy. Used with permission of Royal Society of Chemistry, fromPutro et al (2017); permission conveyed through Copyright Clearance Center, Inc.…”
mentioning
confidence: 99%
“…Most importantly, the existence of oxophilic Fe as a doped additive improves the specific surface area of the catalyst, while the dosage of unsaturated Ni active sites and the distribution of Ni active sites facilitates the adsorption of C = O bonds of FF. Putro et al (2017) adopted a simple hydrothermal method to prepare Ni-Fe alloy catalyst, and used to catalyze the reduction of FF to FFA, acquired excellent performance with a 99% FF conversion and a 95% FFA yield at 150°C for 3 h under a hydrogen pressure of 3 MPa. In order to increase the stability of the Ni-Fe catalyst, some researchers have added some supporters to the catalyst.…”
Section: Catalytic Hydrogenation Of Biofuranic Aldehydes To Alcoholsmentioning
confidence: 99%